Sosialisasi Upaya Menagani Penyalahgunaan Media Sosial di Kalangan Masyarakat Di Desa Sidorejo Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah - By Kasdi; Subiato Subiato; Tri Purwanti; Ditasman Ditasman; Yohanes Susanto (Jurnal Semarak Mengabdi, 2023)
Social media has an influence on the larger community that is both beneficial and harmful. They help the process in real life by providing quick and comprehensive information. Additionally, owing to technical advancements that affect how simple it is to utilize social media as a communication tool, their negative consequence will be to abuse social media through crimes, fraud, and defamation. In order to help the community utilize social media responsibly, this community service aims to contribute perspective, knowledge, and understanding. This community service project is conducted in the form of socialization utilizing the lecture-based approach of information exchange, which is followed by a Q&A session or conversation between presenters and participants.The outcomes of this community service demonstrate that the community's intense use of social media must be consistent with knowledge of safe and responsible use. Through this community service project, it is intended that more individuals will learn how to use social media responsibly, enabling them to make the most of it while minimizing its negative consequences on real-world interactions.